Peran Perempuan dalam Meningkatkan Penghasilan Keluarga Melalui Pengelolaan Jagung Titi di Desa Kolipadan Kecamatan Ile Ape Kabupaten Lembata Provinsi Nusa Tenggara Timur - Maria Imakulata Pongge; Enike Tje Yustin Dima (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2023)
In Kolipadan Village, Ile Ape District, Lembata Regency, the emphasis on family economic capability has created chances for women to maximize the varied family welfare potentials. Several factors include husbands who have passed away, husbands who don't have a stable career, and husbands who earn a livelihood overseas (migration). To help raise family income, a variety of initiatives and opportunities are used, including the regional specialty, namely titi corn, also known locally as Wata Kena'e in Kolipa Village and Ileape District, Lembata District. This study seeks to understand the role of female heads of home in boosting family income to satisfy family requirements through selling titi corn. In this study, the sale of titi corn in particular, is examined, along with the selling price and technique of processing. Both primary and secondary data were used in this investigation. Interviews with 25 female head-of-household respondents in Kolipadan Village provided the primary data. Secondary data comes from data-related offices, namely population density and the number of female workers. A qualitative technique and descriptive analysis were both used in the data analysis for this investigation. The findings demonstrated that women significantly contribute to raising family income by processing corn titi. For one kilogram of corn, titi corn processing costs IDR 10,000 in raw materials and takes a half-day to complete. Titi corn is sold for between IDR 50,000 and IDR 100,000 per kilogram. Monthly revenue from corn sales ranges between IDR 500,000 and IDR 1,500,000. In order for the family to be able to meet its fundamental needs, social and psychological needs, and developmental needs and be considered affluent, women must be the head of the household and must work to improve the family's economics.